Perspektif Mahasiswa Mengenai Dampak Lagu Hello Kuala Lumpur Terhadap Wawasan Nusantara - Nur Heny Anelia Utami; Ratnasari Ratnasari; Zahrani Huraiyah Nurramadhan (Pusat Riset dan Inovasi Nasional, 2024)
The objectives of this study are as follows: (1) To find out whether students understand Archipelago Insight in the Citizenship course, (2) To find out whether students understand the problems associated with the emergence of the Hello Kuala Lumpur song, (3) To find out how students see the impact of the emergence of the Hello Kuala Lumpur song on Archipelago Insight, and (4) To find out how students see Archipelago Insight from a student perspective. The study was conducted from May 10, 2024, to May 15, 2024. Some students from Raja Ali Haji Maritime University and other universities have responded through Google form space. This research with a descriptive qualitative approach aims to produce systematic general information or detailed descriptions that are factual and accurate using natural conditions (without experimental situations). The students already understand what Archipelago Insight is, the ongoing problem, and the consequences of the problem. To mitigate or overcome the effects, there are many ways. For example, better legal protection, education, and socialization on strengthening the insight of the archipelago, cultural cooperation with neighboring countries, improved communication between the Indonesian and Malaysian governments, and support online cultural education platforms.